Evaluation of collaborative consumption of food delivery services throughweb mining techniques - Correa, Juan C.; Garzón, Wilmer; Brooker, Phillip; Sakarkar, Gopal; Carranza, Steven A.; Yunado, Leidy; Rincón, Alejandro (Elsevier, 2019)
Online food delivery services rely on urban transportation to alleviate customers' burden of traveling in highly dense cities. As new business models, these services exploit user-generated contents to promote collaborative consumption among its members. This study aims to evaluate the impact of traffic conditions (through the use of Google Maps API) on key performance indicators of online food delivery services (through the use of web scraping techniques to retrieve customer's ratings and the physical location of restaurants as provided by Facebook). From a collection of 19,934 possible routes between the physical location of 787 online providers and 4296 customers in Bogotá city, we found that traffic conditions exerted no practical effects on transactions volume and delivery time fulfillment, even though early deliveries showed a mild association with the number of comments provided by customers after receiving their orders at home.

Los servicios de entrega de alimentos en línea dependen del transporte urbano para aliviar la carga de los clientes de viajar en ciudades muy densas. Como nuevos modelos de negocio, estos servicios explotan contenidos generados por los usuarios para promover el consumo colaborativo entre sus miembros. Este estudio tiene como objetivo evaluar el impacto de las condiciones del tráfico (mediante el uso de la API de Google Maps) en los indicadores clave de rendimiento de los servicios de entrega de alimentos en línea (mediante el uso de técnicas de raspado web para recuperar las calificaciones de los clientes y la ubicación física de los restaurantes según lo proporcionado por Facebook ). A partir de una colección de 19,934 rutas posibles entre la ubicación física de 787 proveedores en línea y 4296 clientes en la ciudad de Bogotá, encontramos que las condiciones del tráfico no ejercieron efectos prácticos sobre el volumen de transacciones y el cumplimiento del tiempo de entrega, aunque las entregas tempranas mostraron una asociación leve con el número. de los comentarios aportados por los clientes tras recibir sus pedidos en casa.
Keywords: Aplicaciones web; Software de aplicación; Negocios; Redes sociales en línea en los negocios; Online social networks in business; Collaborative consumption; Traffic conditions; Google maps; Online food ordering